An Adaptable Tough Elastomer with Moisture‐Triggered Switchable Mechanical and Fluorescent Properties. (11th July 2019) - Zhou, Xing; Wang, Libing; Wei, Zichao; Weng, Gengsheng; He, Jie
Abstract: Smart materials with coupled optical and mechanical responsiveness to external stimuli, as inspired by nature, are of interest for the biomimetic design of the next generation of soft machines and wearable electronics. A tough polymer that shows adaptable and switchable mechanical and fluorescent properties is designed using a fluorescent lanthanide, europium (Eu). The dynamic Eu‐iminodiacetate (IDA) coordination is incorporated to build up the physical cross‐linking network in the polymer film consisting of two interpenetrated networks. Reversible disruption and reformation of Eu‐IDA complexation endow high stiffness, toughness, and stretchability to the polymer elastomer through energy dissipation of dynamic coordination. Water that binds to Eu 3+ ions shows an interesting impact simultaneously on the mechanical strength and fluorescent emission of the Eu‐containing polymer elastomer. The mechanical states of the polymer, along with the visually optical response through the emission color change of the polymer film, are reversibly switchable with moisture as a stimulus. The coupled response in the mechanical strength and emissive color in one single material is potentially applicable for smart materials requiring an optical readout of their mechanical properties. Abstract : A new design of a Eu‐containing tough elastomer that shows coupled optical and mechanical responsiveness to external stimuli (moisture, pH, ions, etc.) is reported. The mechanical states of the polymers, along with the visually optical response through the emission color change of the polymer film, are reversibly switchable.